Rogowski Electronic Transformer Performance Evaluation and Its Impact on PMUs. Issue 27 (2016) - Bi, Tianshu; Sun, Fei; Liu, Hao; Martin, Kenneth E.; Li, Jinsong
Abstract: As an important component of process level in the smart substation, the electronic transformer is fundamental for the monitoring and control of the smart grid. In this paper, the transformation characteristics of the Rogowski electronic transformer under both static and dynamic conditions, as well as its impact on Phasor measurement units (PMUs), are studied by the theoretical analysis, simulations, and experiments. It can be concluded that the electronic transformer has a good amplitude and frequency response, and it can track the static and dynamic phasor. However, the DC offset and the harmonic components brought by the electronic transformer affect the frequency and the rate of the change of the frequency estimations performed by PMUs.